Is investment in Indigenous land and sea management going to the right places to provide multiple co-benefits?. Issue 3 (2nd July 2020) - Pert, Petina L.; Hill, Rosemary; Robinson, Catherine J.; Jarvis, Diane; Davies, Jocelyn
ABSTRACT: Indigenous land and sea management (ILSM) has been the focus of large government investment in Australia and globally. Beyond environmental benefits, such investments can deliver a suite of social, cultural and economic co-benefits, aligning with the objectives of Indigenous communities and of governments for culturally appropriate socio-economic development. Nevertheless, there have been very few studies done on the spatial distribution of this investment and the extent to which its associated co-benefits address socio-economic disadvantage, which is unevenly distributed across Australia. This study draws on Australian ILSM programmes to examine the spatial and temporal distribution of investment for ILSM between 2002–2012 and considers implications for the distribution of associated co-benefits. Mapping and analysis of 2600 conservation projects revealed that at least 462M of investment in ILSM projects had occurred at 750 discrete sites throughout Australia. More than half of this investment in ILSM has been concentrated in northern Australia, in disadvantaged remote and very remote areas where a high percentage of the population is Indigenous, and Indigenous land ownership extensive. Our research has shown that ILSM investment has successfully been spatially distributed to areas with high needs for multiple social, economic, environmental and health and well-being co-benefit outcomes.